P226 Self-esteem, body image, and subculture identification among gay, bisexual, and other men who have sex with men. (14th July 2019) - Card, Kiffer; Armstrong, Heather; Pan, Shenyi; Blackwell, Everett; Greatheart, Marcus; Moore, David; Hogg, Robert; Roth, Eric; Lachowsky, Nathan
Abstract : Background: Previous research shows that low self-esteem may negatively affect self-efficacy, increase substance use, and underlie some patterns of risky sexual behaviour. This suggests low self-esteem may hinder the prevention of HIV and other sexually transmitted infections (STI). Therefore, we explored factors related to self-esteem among gay and bisexual men (gbMSM), including associations with risk behaviour. Methods: Between 2012–2015, we used respondent-driven sampling to recruit sexually-active HIV-positive and HIV-negative gbMSM, aged > 16 in Metro Vancouver. Participants completed visits every 6-month until 2018. Generalized estimating equations identified correlates of self-esteem (study α =.90, range = 0–21), including key measures of sexual behaviour, substance use, social embeddedness, body image, and sub-cultural identification. Results: Among 541 participants, 3, 497 visits (Median: 7, Q1 -Q3 :[3–9]). In bivariable analyses, self-esteem scores did not differ by HIV-status (p = 0.59), and were not associated with seroadaptive behaviour (p>0.19 across 7 strategies). After adjustment, higher self-esteem was associated with older age (p<0.001), more social support (p<0.001), larger social network size (p<0.003), lower emotional and social loneliness (each p<0.001), Asian (p=0.002) or Latin American (p=0.001) identity (vs. White), higher self-report physical attractiveness (p<0.005) and muscularity (p<0.001), and subcultural identification as a Professional (versus not; p=0.04). While higher BMI was not associated with self-esteem (p=0.94), identifying as a bear, cub, or otter (versus not; p = 0.009) predicted lower self-esteem scores. Self-esteem was associated with several sexual (e.g., oral sex, masturbation, sex toy use) and substance use (i.e., binge drinking, cannabis, cocaine, methamphetamine) behaviours – but these became non-significant after multivariable adjustment. Conclusion: Subculture identification, self-rated body-image, and social embeddedness are key to gbMSM's self-esteem. Given these factors overshadowed self-esteem's association with sexual and substance use behaviours, holistic HIV and STI interventions should leverage socially-supportive, community-based, and inclusive messaging to address potentially negative effects of low self-esteem on gbMSM's sexual health. Disclosure: No significant relationships.